Non-small cell lung cancer harboring EGFR G724S mutation and exon 19 deletion responded to afatinib monotherapy after multiple lines of target therapies. Issue 9 (12th August 2022) - Cortiula, Francesco; Pelizzari, Giacomo; Corvaja, Carla; De Maglio, Giovanna; Fasola, Gianpiero
Abstract : Epidermal growth factor receptor (EGFR) G724S mutation represents a resistance mechanism to first- and third-generation EGFR tyrosine kinase inhibitors. Limited data are available regarding the efficacy of afatinib in patients with non-small cell lung cancer (NSCLC) harboring G724S mutation, particularly after osimertinib. A patient diagnosed with advanced EGFR-mutated (exon 19 deletion) NSCLC after several lines of treatment – gefitinib, osimertinib, heat shock protein inhibitors and chemotherapy-developed EGFR G724S mutation retaining the exon 19 deletion. She was then treated successfully with afatinib leading to a progression free survival of 9 months (and counting). This is the first report of the emergence of G724S mutation, together with ex19del, after three subsequent lines of therapy following progressive disease to Osimertinib, and we report for the first time the activity of afatinib against EGFR exon 18 G724S mutation in this setting.